Obtenção de um catalisador insolúvel para a produção de D-tagatose por L-arabinose isomerase - Sousa, Marylane de (2015)
Within the current therapeutic options for treatment of patients with congenital metabolic problems, diet is the most important pillar and D-tagatose has attracted great attention in recent years because of its benefits to human health and due to its similarities with sucrose. Among its many applications, it emphasizes the potential to assist in weight management, a growing concern in Brazil, since obesity is growing at alarming rates. However, L-arabinose isomerase, the enzyme that catalyses the isomerization of D-galactose into D-tagatose, is not yet commercially available and therefore studies in order to obtain this biocatalyst are necessary in order to enable the implementation of the industrial process. Therefore, in this work, the production of L-arabinose isomerase by Enterococcus faecium was investigated. The produced enzyme was characterized and immobilized onto chitosan. Results of thermal, operational stability and self-life obtained by using L-AI, covalently immobilized onto chitosan in an alkaline medium (pH 10), confirmed the importance of the pH during immobilization, since multipunctuality is favored compared to pH 7.0. Nevertheless, enzyme concentration after fermentation was low and, therefore, we have studied the production of heterologous enzyme in Escherichia coli. The expressed recombinant proteins were purified by affinity chromatography by a single step, and displayed as a single band on SDS-PAGE. The successful construction of the gene and cloning into expression vectors in E. coli resulted in higher amount of the recombinant proteins, which are soluble, easily purified and active, allowing their characterization. Through analytical ultracentrifugation, it was possible to find that the recombinant L-AI has a tendency to form larger structures (oligomers). Multifunctional supports were prepared to L-AI immobilization, allowing achieving high yields (more than 75%) at short contact times. Due to the low thermal stability of the immobilized enzyme, future studies will be needed to stabilize its quaternary structure